Numerical simulations of elliptic vortex-ring interactions - Ng, Teck Li (Nanyang Technological University, 2023)
The interaction between two identical elliptic vortex rings were simulated using Large Eddy Simulation in this numerical study for two different scenarios. One with the major axes initially aligned and another with an azimuthal angle offset between their major axes. Results show that a head-on collision without an azimuthal offset produced a pair of sub-elliptic that propagated apart orthogonal to the direction of the initial direction of travel. When initiated with 90 degrees offset in the azimuthal angle, the collision generated a pair of elongated sub-elliptic that also travelled apart perpendicularly on the other axis. The sub-elliptic ring subsequently further split into tertiary rings. These findings may provide insights on certain interaction of vortices.